2011
DOI: 10.1107/s0909049511011071
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of anisotropic properties of dental enamel from synchrotron data

Abstract: Obtaining information about the intrinsic structure of polycrystalline materials is of prime importance owing to the anisotropic behaviour of individual crystallites. Grain orientation and its statistical distribution, i.e. the texture, have an important influence on the material properties. Crystallographic orientations play an important role in all kinds of polycrystalline materials such as metallic, geological and biological. Using synchrotron diffraction techniques the texture can be measured with high loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Nanoindentation test is an emerging technique for mechanical property evaluation. With the development of thin‐film materials (Nix,1997) and an increased interest in the surface properties of materials, nanoindentation test has increasing partially, because microhardness testing has frequently proven to be inadequate for the small scales that are important in these fields, and human enamel is an anisotropic composite, consisting of aligned prism rods with protein‐rich sheath (Raue and Klein,2011).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoindentation test is an emerging technique for mechanical property evaluation. With the development of thin‐film materials (Nix,1997) and an increased interest in the surface properties of materials, nanoindentation test has increasing partially, because microhardness testing has frequently proven to be inadequate for the small scales that are important in these fields, and human enamel is an anisotropic composite, consisting of aligned prism rods with protein‐rich sheath (Raue and Klein,2011).…”
Section: Discussionmentioning
confidence: 99%
“…The lower values in the other measured positions represent a lower demand of strength in that position. Combining the information about the degree of orientation with the spatial orientation of the maximum values and the type of orientation (tilted fibre texture: Raue,2008;Raue and Klein,2010;Raue and Klein 2011), one can deduce the orientation of the enamel prisms (since the HA crystallites link up along their c-axis, Poole and Brooks,1961), the inner building structure of the prisms and one can also justify the orientation of the prisms with the mechanical needs which have to be fulfilled. Looking at point A to F in the molar (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Something to consider, Dr. Nakabayashi reported that the general breaking (cohesive) capacity of normal human dentine is approximately 21-megapascals (MPa) [90,91] . On the other hand, the calculated modulus of enamel is up to 155 GPa & the thermal expansion is up to 2.3 X 10 [92]. In 1956, Craig & Peyton demonstrated that enamel & dentine have regional density extremes, which they demonstrated by Knoop indentation tests [93].…”
Section: Does An Ideal Alternative In Vitro Biocompatibility Tests Exmentioning
confidence: 99%